Strategy and tactics in sports from an ecological-dynamical-perspective: What is in there for coaches and players? - Buekers, M.; Montagne, G.; Ibáñez-Gijón, J. (Movement & Sport Sciences - Science & Motricité, 2020)
In sports, strategy and tactics play a decisive role. This is certainly so in sport games like volleyball in which the players need to promptly adapt their actions to the continuously changing game situations. In this paper, we will take a closer look at how strategic and tactical decisions come about. Our goal is twofold. First, we want to tackle this discussion from the angle of the ecological-dynamical approach, in which concepts as perception-action coupling, affordances, and self-organization are put forward as vital elements to explain the control of actions/sport skills. In referring to animal behavior, we will push the idea that cognitive interventions are not a prerequisite for strategic and tactical interventions. Second, we want to translate these theoretical concepts into some general guidelines for coaches and practitioners. In doing so, we hope to increase the understanding that for practice the environmental constraints should be embraced in order to improve the strategic and tactical capacities of the players.